CONCEPTUALIZING AN INTEGRATED MANAGEMENT AND INNOVATION MODEL FOR ARCHITECTURAL AND CONSTRUCTION SECTOR DEVELOPMENT WITHIN THE INNOVATIVE, ORGANIZATIONAL, COMMUNICATIVE AND ECONOMIC MANAGEMENT PARADIGM - MAKATORA, Dmytro; KUBANOV, Ruslan; MYKHALKO, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates and conceptualizes an integrated management and innovation model for the development of an architectural and construction company in the context of digital transformation, socio-economic challenges, and spatial renewal. The proposed approach is based on the application of the innovative, organizational, communicative and economic management paradigms, which makes it possible to develop a holistic strategy for the company’s adaptation to market demands, stakeholders, and global sustainable development trends. The model comprises four interrelated blocks: target, content-organizational, technological, and control-diagnostic. Its structure involves the implementation of seven key components: innovation (BIM, Lean, Smart technologies), organizational flexibility, communication strategy, value-based management, corporate social responsibility (CSR), economic efficiency, and managerial professional competence. Each of these elements is presented with regard to current technological, managerial, and social trends. To assess the level of implementation of the model’s components, the article proposes a methodology for constructing the Integrated Implementation Metric (IIM). IIM is calculated based on expert-defined weighting coefficients and quantitative evaluations of each element of the model. This approach enables a comprehensive multifactor diagnosis of the company’s management system, identification of strategic development reserves, and the formation of adaptation mechanisms to a dynamic environment. The model has been partially tested using the example of the company “UVT GROUP”, which demonstrates an advanced level of implementation of managerial and innovation strategies (IIM = 0.752). The study proves that the integration of digital technologies, value-based management practices, and social responsibility strengthens competitive positions, builds social capital, and promotes the sustainable development of the architectural and construction business.
Keywords: integrated management and innovation development model; architectural and construction company; innovative; organizational; communicative and economic management paradigm; innovation; digital transformation; IIM (Integrated Implementation Metric); BIM; social responsibility; communication strategy; value-based management; sustainable spatial development